61.9k views
19 votes
Explain why solving the equation - 3n - 4 = 2 is different from solving the

inequality -3n - 4 < 2. How are the answers different?


please this is due in a few hours !!

User Shadyyx
by
5.1k points

1 Answer

10 votes

Answer:

Explanation:

First get the answer to -3n - 4 = 2

-3n - 4 + 4 = 2 + 4

-3n = 6

n = 6/-3

n = -2

That answer is the only one that is permitted. It is the only one that completely satisfies the equation.

Now when you do the inequality, look what happens.

-3n - 4 < 2 Add 4 to both sides.

-3n-4+ 4 < 2+4

-3n < 6 Now there are a bunch of ways (2) to solve this.

No matter which way you do it, the arrow will change.

-3n/-3 > 6/-3

n > - 2

That means that any number that is greater than - 2 will satisfy the inequality.

So n = 0 will work. Even n = - 1 will work. Anything bigger than -2 will work. The equation does not provide that kind of latitude.

User Ford Guo
by
5.1k points